Scalable Fabrication Of Nickel Micropillars Using Ultra-Violet Photolithography Process For Microelectronics Application - Taufik, Rais Ahmad (Universiti Sains Malaysia, 2019)
In the world of semiconductors and microelectronics, a trend to vertically stack integrated circuits are highly been used as it can meet the electronic device requirements. This stacking system technology can perform better performance, increase the functionality, reduce power consumption and also reduce in size with smaller footprint. There are some methods and processes need to go through in order to achieve the stacking technology that are called 3D integration technologies which addresses Moore law to fit in more ICs/transistors in a smaller area (chip). The overall of this project is being conducted is to develop nickel micropillar on copper substrate by conducting UV lithography of thick SU-8 photoresist pair with nickel electroforming method. Both experimental methodology was conducted step by step in order to study the physio-chemical characterization of the nickel micropillar as a solder interlayer between copper and microbumps to reduce intermetallic compounds to enhance the reliability of joints. This research covers the Ni micropillars just beneath the microbumps. The size of the designed micropillar were within 2 to 80 μm with highest thickness can be achieved. There are experimental methodology that need to conduct in sequence in order to achieve the objectives of this project. The process involved was lithography and nickel electrodeposition. Both this method are the requirement of this project since without the lithography process, there is no SU-8 PDMS mold, without the nickel electrodeposition, there is no growth of nickel form on the copper substrate. Microanalysis of the specimen was conducted by using Scanning Electron Microscopy (SEM) with the Energy Dispersive X-ray Spectroscopy (EDS). All the nickel physical behavior can be analyses through this process.